Development of a highway safety manual - Hughes, Warren (Research results digest (National Cooperative Highway Research Program), 2004)
"This digest represents the results of NCHRP Project 17-18(04), 'Development of a highway safety manual.' This study developed an annotated outline, prototype chapter, and work plan for the first edition of the Highway safety manual. ..."--P. [1].